Regional Climate Protection in Times of Crisis? A comparative study of ten districts in four German Federal States - Zeigermann, Ulrike; Böcher, Michael; Benz, Julia (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
The amended German Climate Protection Act of 2021 is seen as an essential step towards fulfilment national climate protection targets and as a sign of mainstreaming climate protection in German politics. However, at the regional level, where many climate protection measures are implemented, there is a strong fragmentation in terms of priorities, policy instruments, actor constellations and resources. Moreover, the implementation of climate protection measures is under increasing pressure in the face of crises, such as the management of the Covid 19 pandemic or the energy crisis. We therefore ask: Under what conditions does regional climate protection succeed in times of crisis? Drawing on the regional governance concept and a comparative analysis of ten German counties, we explain differences in subnational climate governance. For our study, very different, but always rural districts were selected, as the importance of rural regions is often neglected in the study of local climate policy. Based on a qualitative document analysis in combination with observations and interviews with climate protection managers, we identify factors for the success of climate protection activities in times of multiple crises. We argue that structural factors are central to the success of regional climate protection measures in times of crisis, as they provide the framework conditions for the actions of actors.